Pengaruh Tingkat Pendidikan Dan Penggunaan Informasi Akuntansi Terhadap Keberhasilan Umkm - Rika Syahadatina; Purwanto; Isnain Bustaram (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to determine and analyze the effect of education level and use of accounting information on the success of MSMEs in micro, small and medium enterprises. This study used a population of 45 traders who were at the Trunojoyo Sampang monument, the sampling method was purposive sampling, namely 35 traders. Data was obtained by distributing questionnaires to traders at the Trunooyo Sampang monument. The results of this study indicate that the level of education and the use of accounting information have a significant effect on the success of MSMEs.